Por civismo ou por amor? um estudo sobre as relações existentes entre motivação do trabalho voluntário e cidadania em ONGs de educação no Estado da Paraíba - Ferraz, Tairine Vieira (2017)
This study aimed to reflect on the relationship between voluntary work motivation and its impacts on citizenship in the context of organizations linked to education and research in the state of Paraíba. We sought to identify the voluntary motivations, how each of them affects the citizens attitudes and behaviors and the citizenship expressions as a group of nonvolunteers. The theoretical reference allowed to explore the conceptions of citizenship and its construction in Brazilian's scenery. It also enabled to comprehend the volunteers as key-agent of citizenship participation and as motivational values that influence the type of commitment. Thus, through statistical techniques as correlations and tests for average variations between groups, the relations could be plotted. The results point out that the more constant motivations for the group of volunteers were centered in the learning and altruistic factors , respectively. The results also point that there is the tendency for the group of volunteers to express more actively citizens attitudes and behaviors, mainly in the dimensions related to social rights and the informal participation. Finally, it was possibly to map positive and significant associations to the voluntaries that express altruist reasons in relation to the social, civil and political dimension of the citizenship. It indicates, safeguarded the due proportions that the exercise of the voluntary action would have the role of leading development of a citizenship more active and participant. The work contributes effectively to the management of the volunteers in nongovernmental organizations bound to education, it contributes to the insertion to the debate about ways of encouragement to develop the civic awareness and includes debating about the citizen participation as an important theme to debate in an academic environment.